2021
DOI: 10.1371/journal.ppat.1009708
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-independent functions of B cells during viral infections

Abstract: The humoral immune response and antibody-mediated functions of B cells during viral infections are well described. However, we have limited understanding of antibody-independent B cell functions, such as cytokine production and antigen presentation, in acute and chronic viral infections and their role in protection and/or immunopathogenesis. Here, we summarize the current literature on these antibody-independent B cell functions and identify remaining knowledge gaps. B cell subsets produce anti- and pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 99 publications
0
25
0
Order By: Relevance
“…B cells also contribute to antiviral immunity through mechanisms other than antibody production, including cytokine secretion and presentation of antigen to T cells [ 39 ]. ABCs secrete an array of cytokines with substantial production of IFNγ, tumor necrosis factor (TNF), and interleukin 6 (IL-6) [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…B cells also contribute to antiviral immunity through mechanisms other than antibody production, including cytokine secretion and presentation of antigen to T cells [ 39 ]. ABCs secrete an array of cytokines with substantial production of IFNγ, tumor necrosis factor (TNF), and interleukin 6 (IL-6) [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there was a correlation between eosinophils and B cells in this study. Recent studies [21][22][23] have found that there is a correlation between B cells and viral infections because B cells can secrete interleukin-10 (IL-10), IL-35 and transforming growth factor-β and play a negative immunomodulatory role. This reminds us that we should pay attention to the role of innate immunity in VZV infection, as this will be helpful in judging the severity of the disease and selecting appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques with single cell resolution are required to uncover the contributions of individual clones to the polyclonal ASC pool, the prevalence of specific groups of ASC, and the relationships between the factors and markers that differentiate ASC. It should be noted that many other soluble effectors besides antibodies are also known to be secreted from ASC (12,13), including various interleukins and transforming growth factor-beta one (TGF-b1), and HT functional assays may also be readily adapted to study the role of these soluble factors.…”
Section: Functional Analysesmentioning
confidence: 99%